Pengaruh Kompensasi, Kecerdasan Emosional dan Gaya Kepemimpinan terhadap Kinerja Pegawai pada Bulog Subdivre Lampung Tengah - Fadila, Rezza; Rahayu, Sri Retnaning (Jurnal Manajemen DIVERSIFIKASI, 2021)
Bulog Sub Divre Central Lampung is one of the state-owned institutions which has the main objective of securing food supply and stabilizing rice prices, especially in the central and surrounding areas of Lampung. For that we need employees who have good performance to make this happen. The purpose of this study was to determine the effect of compensation, emotional intelligence and leadership style on employee performance at Bulog Sub Divre Lampung Tengah. This type of research is quantitative research or verification research. The method used in this research is explanatory survey method. The objects in this study are compensation, emotional intelligence, leadership style and employee performance. The population of this research is the employees of Bulog Sub Divre Central Lampung with a total sample of 30 respondents. The data collection technique used a questionnaire. The analytical tool used is to use data quality analysis and multiple linear regression analysis with the SPSS program. The results showed that partially compensation, emotional intelligence and leadership style affect employee performance. Simultaneously it also shows that compensation, emotional intelligence and leadership style together have an effect on employee performance. Based on the significance figures, it can be seen that the factor that most influences employee performance is compensation